Encontros e desencontros nos assentamentos de reforma agrária: estudo sociológico sobre gerações e identidades - Arbarotti, Alexsandro Elias (2014)
After some decades since the establishment of the first settlements the question on its continuity as a public policy arises. Thereby, the research sought to investigate how the generational encounters and disagreements in the settlements of agrarian reform took place. Elements that enabled to understand the historic process experienced by these subjects were sought considering their trajectories and experiences. For this purpose the privileged methodological instrument used was oral history through interviews, material that is enriched with secondary data and bibliography. The field research occurred at "Reunidas gathered" in the municipality of Promissão, SP, and enabled to realize that the subjects' motivation to permanence primarily involved the identification with the locality as a place of sossego and tranquility. However, this identity cannot be thought as something fixed, but in transit and constantly reformulated in relation to the place that is, was and tries to be, i.e., a fanciful, plural, contradictory and temporary identity. In consequence of this reformulation, strategies of permanence indicate new forms of work and income that does not necessarily involve agriculture. And finally, this historic moment of transition and generational coexistence revealed significant changes and ressignifications with regard to projects of life and a vision of land and labor when compared to second generation was the first.